How Does Governance, Individual Internal Factors and Supervisory Functions Affect the Quality of Savings and Loans Cooperative Financial Reports? - Sagung Oka Pradnyawati; Putu Keprameni; Anak Agung Istri Leonika Darmaputri (AIBPM Publisher, 2023)
Cooperatives are essentially a financial institution that functionally plays a major role in the running of the economy in micro-regions that cannot be reached by banks. In 2022 hundreds of cooperatives in Karangasem district will not carry out financial reporting which will have an impact on public confidence in the sustainability and security of cooperative financial conditions. The author aims to analyze empirically whether management, individual factors from the cooperative and the existence of supervisors can affect the quality of a financial report which will be an indicator of performance evaluation at the annual member meeting. Cooperatives in the sidemen sub-district of Bali province are used as research areas. The data was obtained directly from 30 respondents who are cooperative staff and come from ten active cooperatives in the sidemen area. Data collection was supported by a paper questionnaire and analyzed using the regression method. The results of the tests conducted found that corporate governance as measured by good corporate governance and individual factors as measured using education and level of understanding of accounting had a positive impact on the quality of financial reports in contrast to the function of the oversight body and individual factors as measured using work experience did not show any impact significant.